Characterization of melanin pigment produced by Aspergillus nidulans - Goncalves, R. C. R.; Lisboa, H. C. F.; Pombeiro-Sponchiado, S. R. [UNESP] (Springer, 2012)
Although most of the Ascomycetes present DHN-melanin, some reports suggest that A. nidulans does not produce this type of melanin. In this study, we analyzed the pigment extracted from highly melanized strains (MEL1 and MEL2) of Aspergillus nidulans to determine the type of melanin present in this fungus. Our results showed that the pigment produced by MEL1 and MEL2 mutants possesses physical and chemical properties and UV- and IR-spectra very similar to synthetic DOPA-melanin. The characterization of this pigment in terms of its degradation products indicated the presence of indolic units, which were also found in synthetic DOPA-melanin. The analyses of the elemental composition showed that the pigment extracted from these mutants has a high percentage of nitrogen and, therefore, it cannot be DHN-melanin, which presents only trace of nitrogen. This observation was confirmed in the test with tricyclazole because this inhibitor of DHN-melanin biosynthesis did not suppress pigment production in the MEL1 and MEL2 strains. on the other hand, in a medium containing tropolone, an inhibitor of DOPA-melanin biosynthesis, the dark pigmentation of the colonies was not observed indicating that this compound inhibited melanin production in these strains. Taken together, the results obtained in this study indicate that melanin produced by these mutants is DOPA type, representing the first report on characterization of this type of melanin in A. nidulans.
Keywords: Aspergillus nidulans; DOPA-melanin; Infrared and ultraviolet spectra; Tricyclazole; Tropolone